Exploration of Individual and Family Factors Related to Community Reintegration in Veterans With Traumatic Brain Injury. (May 2015) - Moriarty, Helene; Winter, Laraine; Robinson, Keith; True, Gala; Piersol, Catherine; Vause-Earland, Tracey; Iacovone, Dolores Blazer; Holbert, Laura; Newhart, Brian; Fishman, Deborah; Short, Thomas H.
BACKGROUND: Community reintegration (CR) poses a major problem for military veterans who have experienced a traumatic brain injury (TBI). Factors contributing to CR after TBI are poorly understood.OBJECTIVE: To address the gap in knowledge, an ecological framework was used to explore individual and family factors related to CR.DESIGN: Baseline data from an intervention study with 83 veterans with primarily mild to moderate TBI were analyzed. Instruments measured CR, depressive symptoms, physical health, quality of the relationship with the family member, and sociodemographics. Posttraumatic stress disorder and TBI characteristics were determined through record review.RESULTS: Five variables that exhibited significant bivariate relationships with CR (veteran rating of quality of relationship, physical functioning, bodily pain, posttraumatic stress disorder diagnosis, and depressive symptoms) were entered into hierarchical regression analysis. In the final analysis, the five variables together accounted for 35% of the variance, but only depression was a significant predictor of CR, with more depressed veterans exhibiting lower CR.CONCLUSIONS: Efforts to support CR of Veterans with TBI should carefully assess and target depression, a modifiable factor.